2014
DOI: 10.1093/hmg/ddu073
|View full text |Cite
|
Sign up to set email alerts
|

Contesting the dogma of an age-related heat shock response impairment: implications for cardiac-specific age-related disorders

Abstract: Ageing is associated with the reduced performance of physiological processes and has been proposed as a major risk factor for disease. An age-related decline in stress response pathways has been widely documented in lower organisms. In particular, the heat shock response (HSR) becomes severely compromised with age in Caenorhabditis elegans. However, a comprehensive analysis of the consequences of ageing on the HSR in higher organisms has not been documented. We used both HS and inhibition of HSP90 to induce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…This observation has led to the hypothesis that the pathways necessary to maintain proteostasis and suppress protein misfolding and aggregation are progressively compromised with age, eventually leading to disease onset. In support of this idea, reduced expression of molecular chaperones, altered proteasome activity, and disruption of stress responses have been observed in aged rodent tissues and senescent human cells (36, 111, 112). Additionally, an investigation of chaperone and cochaperone gene expression in young (36±4 years of age) and aged (73 ±4 years of age) human brain tissue revealed that of 332 genes examined, 101 are significantly repressed with age, including HSP70, HSP40, HSP90, and TRiC genes (113).…”
Section: Could Programmed Changes In the Proteostasis Network Underlimentioning
confidence: 78%
“…This observation has led to the hypothesis that the pathways necessary to maintain proteostasis and suppress protein misfolding and aggregation are progressively compromised with age, eventually leading to disease onset. In support of this idea, reduced expression of molecular chaperones, altered proteasome activity, and disruption of stress responses have been observed in aged rodent tissues and senescent human cells (36, 111, 112). Additionally, an investigation of chaperone and cochaperone gene expression in young (36±4 years of age) and aged (73 ±4 years of age) human brain tissue revealed that of 332 genes examined, 101 are significantly repressed with age, including HSP70, HSP40, HSP90, and TRiC genes (113).…”
Section: Could Programmed Changes In the Proteostasis Network Underlimentioning
confidence: 78%
“…Regulation of HSF1 and downstream target genes in tissues of HSF1 303A/307A mice during chronological aging under basal conditions or upon exposure to heat-induced stress. An age-related decline in stress response and HSF1 activity has been documented (8,34), but the underlying mechanism remains elusive. Histological sections of organs (cardiac and skeletal muscles, liver, kidney, and brain) from young and aged mice, stained for hematoxylin and eosin (H&E), did not reveal apparent morphological changes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the concentration of TTR in the serum of humans and mice decreases with aging but there are no data available documenting an alteration in neuronal TTR production with increasing age [54,55]. It has previously been suggested that neuronal HSF1 responses, primarily measured in terms of HSP70, are reduced in aged mice but recent data suggest that may not be the case [56,57]. If neuronal TTR production is diminished in aging, whether it reflects reduced HSF1 responsiveness or not, its reduction could contribute to the association of sporadic neurodegenerative disease with age.…”
Section: Discussionmentioning
confidence: 99%